TINDAKAN KEKERASAN OLEH MASSA TERHADAP ORANG YANG TERTANGKAP TANGAN SAAT MELAKUKAN TINDAK PIDANA - Siska Pratini (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractCriminal Acts of Eigenrichting is the term for actions to punish a party without going through a process that is in accordance with the law, this occurs because of the factors that cause lack of legal attention in the community. Law enforcement of the main legal actions of Eigenrichting must be approved, straightforward, and in accordance with the fairness of the value of truth and not in accordance with interests. This is very important in realizing order, legal certainty and peace in society. Based on this background, the discussion in this study is what factors lead to the judge's own actions against expenditures when committing a crime and how to account for lawyers who commit acts of the judge themselves. The method used in this study uses normative research methods. The data used are primary data obtained by interview and secondary data obtained through literature study. While processing data obtained by organizing, editing, classifying and collecting data, and gathering conclusions. The results of the data processing are interpreted descriptively qualitatively by describing quality data in the form of sentences that are resolved, logical and effective so as to facilitate the interpretation and understanding of the results of the analysis in order to answer existing problems. The provisions of Article 170 of the Criminal Code in providing penalties for applications that have been applied to existing problems and applicable law.Keywords: Hand Arrest, Crime